An indicator displacement assay recognizes enantiomers of chiral carboxylates12. Issue 50 (5th June 2019) - Sheykhi, Sara; Mosca, Lorenzo; Durgala, Johnathon M.; Anzenbacher, Pavel
Abstract : Analyte chirality induces changes in fluorescence. Abstract : Two chiral copper(ii )-based receptors—[Cu RR L] 2+ and [Cu SS L] 2+ —in conjuction with the fluorescent indicator coumarin 343 were used to establish an enantioselective indicator displacement assay (eIDA) for the determination of the enantiomeric composition of chiral carboxylates such as ibuprofen, naproxen and atorvastatin.